Critical Analysis of Global Health Trends, Economic Impacts, And Cultural Adaptations in Healthcare - Alotaibi, Ali Muqbil A; Alruwili, Layali Almahdi Eatish; Almutairi, Majed Munhai; Alharbi, Mohammad Abdullah B; Alotaibi, Noura Abdulrhman; Alsaeed, Awatif DhiffAllah; Alrogi, Majed Sagar; Alotaiby, Felwah Gassem; Alharbi, Adel Muqbil Obiad; Alharbi , Abdulaziz Muqbil Obiad (Journal of Ecohumanism, 2024)
Healthcare systems worldwide are confronted with sophisticated issues that have to do with demography, economics, and cultures. The dynamics of these important health trends are analyzed herein, their economic implications assessed, and cultural considerations in the provision of healthcare services discussed. This paper focuses on fair distribution, originality, and financial viability and blends global examples, quantitative data, and qualitative findings to explain effective change. Results reveal that despite the advances in using technology and addressing cultural relevance in delivered interventions, sustained disparities and limited funding require strategic international partnership. Recommendations are on policy support, building and strengthening the capacity of workforce and developing and expanding available technologies.